Factores de riesgo para infección por Pseudomonas aeruginosa multi-resistente en un hospital de alta complejidad (2023)
Introduction: Multi-resistant Pseudomonas aeruginosa (MR) is frequently associated with healthcare infections. Its epidemiology is complex and few studies help to understand it. A study about risk factors associated with this type of bacteria is needed. Objective: To determine risk factors associated with MR P. aeruginosa infection in hospitalized patients from the Hospital Universitario San Vicente Foundation-Medellin. Materials and Methods: case-control study to identify risk factors associated with infection by MR P. aeruginosa. Results: 140 patients were included, 70 in each group. Bivariate analysis found association with previous use of carbapenems (OR 3.12 - IC 1.21 to 8.03, p = 0.02), aminoglycosides (OR 5.09 - CI: 1.38 to 18, 77, p = 0.01) and days of stay prior to isolation of the organism (OR 1.03 - CI: 1.01-1.05, p = 0.01). In multivariate analysis MR P. aeruginosa infection was associated with hospital stay (OR 1.03 - IC 1.01 to 1.05), use of aminoglycosides (OR 1.30 to 19.28) and treatment with two or more antimicrobials in the last 30 days (OR 3.09 - CI: 1.26 to 7.58). The risk of developing infection was 3% per day of hospital stay prior to isolation of the agent. Conclusion: Developing MR P. aeruginosa infection was associated with prior use of antimicrobials and prior hospital stay. © 2014, Sociedad Chilena de Infectologia. All rights reserved.